Ontogeny of Hepatic Drug Transporters as Quantified by LC‐MS/MS Proteomics. Issue 4 (13th August 2016) - Prasad, B; Gaedigk, A; Vrana, M; Gaedigk, R; Leeder, JS; Salphati, L; Chu, X; Xiao, G; Hop, CECA; Evers, R; Gan, L; Unadkat, JD
Abstract : Protein expression of major hepatic uptake and efflux drug transporters in human pediatric ( n = 69) and adult ( n = 41) livers was quantified by liquid chromatography / tandem mass spectroscopy (LC‐MS/MS). Transporter protein expression of OCT1, OATP1B3, P‐gp, and MRP3 was age‐dependent. Particularly, significant differences were observed in transporter expression ( P < 0.05) between the following age groups: neonates vs. adults (OCT1, OATP1B3, P‐gp), neonates or infants vs. adolescents and/or adults (OCT1, OATP1B3, and P‐gp), infants vs. children (OATP1B3 and P‐gp), and adolescents vs. adults (MRP3). OCT1 showed the largest increase, of almost 5‐fold, in protein expression with age. Ontogenic expression of OATP1B1 was confounded by genotype and was revealed only in livers harboring SLCO1B1*1A/*1A . In livers >1 year, tissues harboring SLCO1B1*14/*1A showed 2.5‐fold higher ( P < 0.05) protein expression than SLCO1B1*15/*1A . Integration of these ontogeny data in physiologically based pharmacokinetic (PBPK) models will be a crucial step in predicting hepatic drug disposition in children.